ANALISIS PERBANDINGAN PENGGUNAAN APLIKASI FINTECH DANA DAN OVO BERBASIS ISO 9241-11 MENGGUNAKAN METODE “STATISTICAL PRODUCT AND SERVICE SOLUTION (SPSS)” - Dea Damarista Tarigan; Meta Meysawati; Fauziah; Dina Agusten (Asosiasi Dosen Muda Indonesia, 2024)
Usability is an important aspect in measuring the quality of an application. Applications must have good usability to make it easier for users to operate the application both for use and to obtain the information needed for each user. This study aims to find out how far the application of technological developments in the field of Financial Technology (fintech) DANA and OVO is usable for users based on the usability measurement approach ISO 9241-11 with three measurement indicators, namely effectiveness, efficiency and satisfaction. This research was conducted with data obtained through the help of a questionnaire with a Likert scale consisting of 26 questions grouped into four variables with 400 respondents for each application of 200 respondents based on 7 stages of data testing, namely descriptive statistical test, validity test, test reliability, normality test, variable linearity test, R2 test and the last hypothesis test. The data obtained will be processed and calculated using the help of the Statistical Product and Service Solution version 23 software, with the final result being an average usability value of 53.6% for the DANA application, and 64.4% for the OVO application.